HMGB1 Box A gene therapy to alleviate bleomycin-induced pulmonary fibrosis in rats - Rathasapa Patarat; Suchanart Chuaybudda; Sakawdaurn Yasom; Apiwat Mutirangura (BMC Pulmonary Medicine)
Abstract Background Pulmonary fibrosis is characterized by the destruction of normal lung tissue and then replacement by abnormal fibrous tissue, leading to an overall decrease in gas exchange function. The effective treatment for pulmonary fibrosis remains unknown. The upstream pathogenesis of pulmonary fibrosis may involve cellular senescence of the lung tissue. Previously, a new gene therapy technology using Box A of the HMGB1 plasmid (Box A) was used to reverse cellular senescence and cure liver fibrosis in aged rats. Methods Here, we show that Box A is a promising medicine for the treatment of lung fibrosis. In a bleomycin-induced pulmonary fibrosis model in the male Wistar rats, Student’s t-test and one-way ANOVA were used to compare groups of samples. Results Box A effectively lowered fibrous tissue deposits (from 18.74 ± 0.62 to 3.45 ± 1.19%) and senescent cells (from 3.74 ± 0.40% to 0.89 ± 0.18%) to levels comparable to those of the negative control group. Moreover, after eight weeks, Box A also increased the production of the surfactant protein C (from 3.60 ± 1.68% to 6.82 ± 0.65%). Conclusions Our results demonstrate that Box A is a promising therapeutic approach for pulmonary fibrosis and other senescence-promoted fibrotic lesions.